Phosphorus modified carbon fiber cloth as a robust and efficient anode for alkaline water electrolysis - Zhao, X. (2022)
Developing cost-effective electrocatalysts is critical to renewable energy conversion and storage technologies. In this work, commercial carbon fiber cloth (CFC) was thermally treated with PCl3 in a sealed-tube reactor to obtain phosphorus-modified CFC (P-CFC). The P-CFC can deliver an oxygen evolution reaction (OER) current density of 10 mA cm−2 with only 310 mV overpotential for 50 h with negligible activity decay, which is superior to all other reported metal-free OER electrocatalysts. The mechanism of improved OER activity was systematically studied by electron microscopy and photoelectron spectroscopy. It was found that the p-type doping on the CFC surface by P atom could promote the electron transfer from OH− to the electrode; moreover, the formation of oxidized C–P active sites under anodic potential boosted OER activity both thermodynamically and kinetically. This work not only develops a highly active metal-free OER electrocatalyst but also introduces a promising method to enhance the durability of carbon support for oxidative electrochemical reactions.